Factors Associated With the Implementation of a Nurse Staffing Directive. (December 2017) - Annis, Ann M.; Robinson, Claire H.; Yankey, Nicholas; Krein, Sarah L.; Duffy, Sonia A.; Taylor, Beth; Sales, Anne
Abstract : BACKGROUND: In 2010, the Veterans Health Administration issued a Staffing Methodology (SM) Directive to provide a standardized, data-driven method for determining appropriate inpatient nurse staffing. OBJECTIVE: We aimed to describe experiences and factors related to SM implementation. METHODS: We administered a Web-based survey to chief nurse executives to obtain their implementation experiences. Structural, process, and outcome factors and barriers associated with self-reported implementation success were identified. RESULTS: Respondents representing 104 of 117 facilities participated. Almost all facilities (96%) had completed at least 1 cycle of SM, yet only half (52%) rated their implementation highly successful. Early implementation date, higher levels of leadership confidence in SM, and higher frequency in which nursing staff think in terms of hours per patient day were associated with higher SM implementation success. Time, staff training and educational needs, and engagement were common barriers. DISCUSSION: Understanding factors that influence successful implementation of staffing policies is important to ensuring safe staffing.